2019
DOI: 10.1111/and.13434
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms inRenalaseandKCNQ1genes and female infertility: A cross‐sectional study in Pakistan

Abstract: A global increase in the incidence of subfertility is observed, and research suggests strong genetic influences that might restrict fertility directly or indirectly. It therefore becomes important to rule out the existence of genetic causes and counsel infertile couples before offering “Advanced Infertility Treatment Techniques.” This cross‐sectional study aimed to explore the association of KCNQ1 (rs2237895) and Renalase (rs2576178 and rs10887800) single nucleotide polymorphisms with different causes of infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Among all potentially applicable records only 43 focused on the subject by title and abstract. These papers were screened and divided into three areas: renalase enzymatic activity (16 records), 1,2,4,5,6,7,8,9,10,11,12,13,14,15,16,17 renalase polymorphisms (16 records) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and renalase non-enzymatic activity (11 records). [34][35][36][37][38][39][40][41][42][43][44]…”
Section: Me Thodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among all potentially applicable records only 43 focused on the subject by title and abstract. These papers were screened and divided into three areas: renalase enzymatic activity (16 records), 1,2,4,5,6,7,8,9,10,11,12,13,14,15,16,17 renalase polymorphisms (16 records) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and renalase non-enzymatic activity (11 records). [34][35][36][37][38][39][40][41][42][43][44]…”
Section: Me Thodsmentioning
confidence: 99%
“…Interestingly, both rs2576178 and rs10887800 were suggested to be involved in the pathogenesis of coronary artery disease (CAD). 27,28 Hu et al 27 carried out a case-control study that included a total of 449 CAD patients and 507 healthy controls. Their results revealed that renalase rs2576178 GG (homozygous mutant) was significantly associated with increased risk of CAD (GG compared with AA -wild type, OR = 1.60, 95% CI = 1.07-2.39, P = .022).…”
Section: Renalase -Polymorphysmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study proved a significant correlation of SNPs rs2576178 and rs10887800 with female infertility of unknown cause and with infertility caused by polycystic ovarian syndrome. Scientists have hypothesised that SNPs in the renalase gene may interfere with the hormonal hypothalamic-pituitary-associated ovarian axis by affecting the degradation of catecholamines and increasing the number of stress hormones [47]. The link between renalase and the reproductive system is supported by the fact that Zhou et al proved that the gonads and adrenal cortex are a source of renalase and suggested that it may affect fertility [3].…”
Section: Female Infertilitymentioning
confidence: 99%